1999
DOI: 10.1038/sj.ijo.0800837
|View full text |Cite
|
Sign up to set email alerts
|

Substrate utilization and thermogenic responses to β-adrenergic stimulation in obese subjects with NIDDM

Abstract: OBJECTIVE: This study intended to investigate disturbances in b-adrenergically-mediated substrate utilization and thermogenesis in obese subjects with mild non insulin-dependent diabetes mellitus (NIDDM). DESIGN: Following a baseline period of 30 min, the b-agonist isoproterenol (ISO) was administered in increasing doses of 6, 12, and 24 ngakg FFM .min, each dose for 30 min. SUBJECTS: Nine healthy lean males (CON, 50.6 AE 2.4 y, % body fat: 16.0 AE 1.8) and 10 obese subjects with NIDDM (51.8 AE 2.4 y, % body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…It should be mentioned that there are major differences in catecholamine-induced lipolysis between depots (subcutaneous vs visceral and gluteofemoral) and also gender differences in body fat distribution. [43][44][45] Our data indicate that variability in codon 16 of the ADRB2 gene may contribute to a reduced in vivo b-adrenoceptor-mediated lipolysis and fat oxidation, [1][2][3][4] indicating that these blunted responses may be important primary factors in obesity.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It should be mentioned that there are major differences in catecholamine-induced lipolysis between depots (subcutaneous vs visceral and gluteofemoral) and also gender differences in body fat distribution. [43][44][45] Our data indicate that variability in codon 16 of the ADRB2 gene may contribute to a reduced in vivo b-adrenoceptor-mediated lipolysis and fat oxidation, [1][2][3][4] indicating that these blunted responses may be important primary factors in obesity.…”
Section: Discussionmentioning
confidence: 71%
“…In vivo studies have shown that the development or maintenance of increased adipose tissue stores might be promoted by a blunted lipolytic response and fat oxidation after b-adrenergic stimulation or exercise in obese or obese type 2 diabetic subjects. [1][2][3][4] This blunted b-adrenoceptor-mediated lipolysis and fat oxidation persisted after weight reduction, indicating that this disturbance may be an early, even primary factor, in the development or maintenance of increased adipose stores. 1 There are indications that the blunted b-adrenergically mediated lipolysis in obesity may be related to an impaired function or a reduced number of adipocyte beta-2 (b 2 ) adrenoceptors.…”
Section: Introductionmentioning
confidence: 94%
“…The present study was designed to investigate whether the impaired sympathetically mediated fat oxidation, reported in obese subjects in several studies, 1,5,6,30 could be improved by exercise training independent of changes in body mass and body composition. However, the obese subjects who participated in the present study did not appear to have a blunted b-adrenergically mediated fat oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was in agreement with that previously found in lean. 1,5,6,30 Apparently the effect of b-adrenergic stimulation on fat oxidation is variable in obese subjects. Unfortunately no data were available to compare the level of physical ®tness of the obese subjects in our study with the obese subjects in the studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation